The Boundedness of Marcinkiewicz Integrals Associated with Schrödinger Operator on Morrey Spaces. (20th August 2014) - Chen, Dongxiang; Jin, Fangting
Abstract : LetL = - Δ + V be a Schrödinger operator, whereV belongs to some reverse Hölder class. The authors establish the boundedness of Marcinkiewicz integrals associated with Schrödinger operators and their commutators on Morrey spaces.